COD, BOD and AOX maesurement of filtrates from precipitation of reactive dyes by ionic liquids - Václavíková, Jana; Bandžuchová, Lenka; Mikulášek, Petr (University of Pardubice, 2013)
In this paper, we studied the precipitation efficiency of five anionic reactive dyes dissolved in aqueous solution using two selected quaternary salts, trihexyltetradecylphosphonium chloride (THTDPCl) and Aliquat 336, using spectroscopic measurements of different molar ratios of the dye to ionic liquid. Chemical oxygen demand (COD), biochemical oxygen demand (BOD), and adsorbable organic halogen (AOX) measurements of filtrates from precipitation were performed. The purpose of this study was to investigate the removal efficiency of reactive dyes by ionic liquids based on ammonium or phosphonium quaternary salts. According to the results, neither of the ionic liquids disturbed BOD measurements, indicating that ionic liquids are not among the biocidal substances. The results showed that an increase in the molar ratio of the ionic liquid versus the reactive dye led to a decline in all of the studied parameters.